Coping Strategies in Business from the Viewpoint of Education and Gender - Tatiana PETHO; Róbert ŠTEFKO; Jaroslava GBUROVÁ (Communications of International Proceedings, 2020)
The aim of the research study is to compare traders in the level of coping strategies from the viewpoint of type of education (humanistic and economic university education) and age of traders (traders younger than 40,99 years and traders older than 41 years). Research sample consisted of 143 participants aged from 18 to 65 years (average age was 35.235 with standard deviation of 2.432). Czech version of the German Stress coping style questionnaire SVF 78 (Janke, Erdmann 2003, Janke & Erdmann, 2002) was used for measuring coping strategies. T- test for two independent samples did not find statistically significant differences between traders with humanistic university education and traders with economic university education. The comparison of means of differences found statistically significant differences in the level of substitutional satisfaction (p=0.025). Statistically significant differences were found in the level of guilt rejection in the context of age.
Keywords: coping; coping strategies; business; trader